Implementation Project-Based Learning Model On Electrical Motor Installation - Mustaqim, Bima; Sibuea, Abdul Muin; Siagian, Sahat; Junaidi, Agus; Amin, Muhammad; Baharuddin, Baharuddin; Ampera, Dina (JKTP: Jurnal Kajian Teknologi Pendidikan, 2024)
The learning process in vocational high schools is a determining factor in producing graduates of vocational high schools who are in accordance with their competencies. The learning process will determine whether the learning objectives will be achieved. This study aims to develop a project-based learning device on the installation of electric motors. The method used is User Centered Design with data processed from teachers and students. The results of the implementation of project-based teaching materials for teachers are Good and students are Fairly Good. The project-based learning device is practical enough to make it easier for students to understand the learning of installing electric motors with guidance from teachers. These findings confirm the great usefulness of this model in facilitating a comprehensive understanding of the Installation of Electric Motors. Through its significant role in this subject, this model has developed into a versatile reference model. This model is not only easy to apply in various academic domains, but also effectively enriches students' learning experiences in various subjects. As a result, this model becomes a very valuable tool in supporting a deeper and more holistic learning and teaching process. Abstrak Proses pembelajaran di sekolah menengah kejuruan merupakan faktor penentu untuk dapat melahirkan lulusan pendidikan menengah kejuruan yang sesuai dengan kompetensinya. Proses pembelajaran akan menentukan apakah tujuan pembelajaran akan tercapai. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berbasis proyek tentang pemasangan motor listrik. Metode yang digunakan adalah User Centered Design dengan data yang diolah bersumber dari guru dan siswa. Hasil implementasi bahan ajar berbasis proyek untuk guru adalah Baik dan siswa adalah Cukup Baik. Perangkat pembelajaran berbasis proyek cukup praktis untuk memudahkan siswa memahami pembelajaran pemasangan motor listrik dengan bimbingan dari guru. Temuan ini menegaskan kegunaan besar model ini dalam memfasilitasi pemahaman yang komprehensif tentang Pemasangan Motor Listrik. Melalui perannya yang signifikan dalam subjek ini, model ini telah berkembang menjadi model referensi yang serba guna. Model ini tidak hanya mudah diterapkan di berbagai domain akademik, tetapi juga secara efektif memperkaya pengalaman belajar siswa di berbagai mata pelajaran. Sebagai hasilnya, model ini menjadi alat yang sangat berharga dalam mendukung proses pembelajaran dan pengajaran yang lebih mendalam dan holistik.